A Quantitative Study of Examinees’ Perceptions of the Design and Development of Higher Education Exit Exams: The Case of JIGDAN College - Teshome, Samson Worku; Kibret, Belay Tefera; Fantaye, Girma Lemma (International Journal of Humanities, Education, and Social Sciences, 2025)
This research explores how students perceive the design of exit exam in Ethiopia at JIGDAN College, focusing on the Accounting and Finance and Management departments. Adopting a quantitative case study method, the study assesses the effectiveness, fairness, and overall quality of higher education exit exam design. Data were gathered through structured questionnaires completed by 127 students that took exit exam in 2023 and 2024, yielding critical insights into their experiences. Census was used since the number of students was small. The findings reveal that while students appreciate the clarity of guidelines and the relevance of exam content to their coursework, concerns emerge regarding the representation of diverse backgrounds and the integration of ethical issues. The results indicate a significant need for improved stakeholder involvement to better align assessments with industry standards. Additionally, students expressed a desire for exit exam that incorporate practical applications and ethical dilemmas, highlighting the importance of preparing them for real-world challenges. Recommendations for enhancing exit exam design include increasing clarity and accessibility of guidelines, promoting inclusivity through diverse input, strengthening collaboration with industry stakeholders, and integrating ethical considerations into assessments. By addressing these areas, the Ministry of Education can improve the effectiveness and fairness of its exit exams, ultimately better preparing students for successful careers. This research contributes to the ongoing discourse on exit exam and underscores the necessity of aligning academic evaluations with the evolving demands of the professional landscape. Future studies should explore the implementation of these recommendations and their impact on students’ outcomes and perceptions, fostering a continuous improvement approach to exit exam design.